PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH TABUNGAN PADA PT. BANK MUAMALAT INDONESIA, Tbk CABANG PALU - Lestari, Dian Nurani (Katalogis, 2014)
The  objectives  of  this  research  are  to:  (1)  know  and  analyze  simultaneous  effect  ofrelationship marketing on saving customer loyalty at PT. Bank Muamalat Indonesia, Tbk. Palu Branch, (2) know and analyze partially positive and significant effect of trust, commitment, communication, and conflict handling partially on saving customer loyalty at PT. Bank Muamalat Indonesia, Tbk. Palu Branch. There are 100 Respondents in this study that have been determined as the  sample  using  census  method.  Analysis  method  used  in  this  research  is  multiple  linear regression. The results show that: (1) relationship marketing performs simultaneously effect on customers loyalty at PT. Bank Muamalat Indonesia, Tbk. Palu Branch, (2) trust, commitment, and communication partially performs positive and significant effect on customer loyalty at PT. Bank Muamalat Indonesia, Tbk. Palu Branch, and conflict handling performs positive but not significant effect on customer loyalty at PT. Bank Muamalat Indonesia, Tbk. Palu Branch.